Best Estimate Selection Bias in the Value of a Statistical Life. Issue 2 (9th October 2017) - Viscusi, W. Kip
Abstract : Selection of the best estimates of economic parameters frequently relies on the "best estimates" or a meta-analysis of the "best set" of parameter estimates from the literature. Using an all-set dataset consisting of all reported estimates of the value of a statistical life (VSL) as well as a best-set sample of the best estimates from these studies, this article estimates statistically significant publication selection biases in each case. Biases are much greater for the best-set sample, as one might expect, given the subjective nature of the best-set selection process. For the all-set sample, the mean bias-corrected estimate of the VSL for the preferred specification is $8.1 million for the whole sample and $11.4 million based on the CFOI data, while for the best-set results, the whole sample value is $3.5 million, and the CFOI data estimate is $4.4 million. Previous estimates of huge publication selection biases in the VSL estimates are attributable to these studies' reliance on best-set samples.